2011
DOI: 10.1039/c0cp01985b
|View full text |Cite
|
Sign up to set email alerts
|

Improved light olefin yield from methyl bromide coupling over modified SAPO-34 molecular sieves

Abstract: As an alternative to the partial oxidation of methane to synthesis gas followed by methanol synthesis and the subsequent generation of olefins, we have studied the production of light olefins (ethylene and propylene) from the reaction of methyl bromide over various modified microporous silico-aluminophosphate molecular-sieve catalysts with an emphasis on SAPO-34. Some comparisons of methyl halides and methanol as reaction intermediates in their conversion to olefins are presented. Increasing the ratio of Si/Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
1
25
0
4
Order By: Relevance
“…In general, the hydrothermal conditions of the regeneration may cause a redistribution of silicon atoms into aggregates termed “silicon islands” 9, 10. This will lead to the formation of silanol groups that can be detected with IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the hydrothermal conditions of the regeneration may cause a redistribution of silicon atoms into aggregates termed “silicon islands” 9, 10. This will lead to the formation of silanol groups that can be detected with IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, great efforts have been made towards decreasing deactivation rates and increasing catalyst activity. Critical improvements have been made by modification of the catalyst crystal size and acidity; and an increased catalyst lifetime is reported for smaller crystal size and lower acidity 5, 6, 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Many contributions involving the conversion of chloromethane or bromomethane to olefins over various zeolite catalysts have been made in recent years [36][37][38][39][40][41][42][43]. Su and co-workers comparatively investigated the transformation of chloromethane to hydrocarbons over different zeolite catalysts and proposed the reaction mechanism over SAPO-34 molecular sieve [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Olsbye et al studied the methyl halide to hydrocarbon reaction over HSAPO-34 in experimental and computational methods [41,42]. McFarland et al reported an improved light olefins yield from bromomethane over metal modified SAPO-34 catalyst [43]. In summary, SAPO-34 could be the most promising catalyst in the reaction of methyl halide to give olefins until now, like in the MTO process.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative pathway for methane partial oxidation using bromine, rather than oxygen, has been demonstrated and piloted [5][6][7][8][9]. Bromine can be generated from the reaction of oxygen with hydrogen bromide (HBr), or from many solid metal bromides (MBr 2 ), (reaction 1).…”
Section: Introductionmentioning
confidence: 99%